2006
DOI: 10.1016/j.lisr.2006.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly productivity of U.S. LIS faculty

Abstract: One aspect of faculty effectiveness can be measured through research productivity, and publication and citation rates can serve as an indicator of that productivity. This study, the fourth in a series to examine LIS faculty and program productivity as measured by publication and citation, uses the same methodology as the previous investigations. A consistent data instrument (the Social Science Citation Index) provided publication and citation data for LIS faculty, covering the years 1999 to 2004. Tables show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 10 publications
1
58
0
Order By: Relevance
“…The criteria for selecting journals were guided by the qualities of having a high impact factor, to ensure the journals' representation of major interests among contemporary American sociology given its importance in the American social sciences (Adkins and Budd 2006;Jacobs 2011Jacobs , 2016, and general thematic interests, in principle open to the publication of all topics without overt bias. Keeping this in mind, the American Journal of Sociology, the American Sociological Review, and Social Forces were selected to best ensure that any trends identified actually reflect voluntarily decided interests among American sociologists from 1950 -the heyday of American sociology -to 2010.…”
Section: Samplementioning
confidence: 99%
“…The criteria for selecting journals were guided by the qualities of having a high impact factor, to ensure the journals' representation of major interests among contemporary American sociology given its importance in the American social sciences (Adkins and Budd 2006;Jacobs 2011Jacobs , 2016, and general thematic interests, in principle open to the publication of all topics without overt bias. Keeping this in mind, the American Journal of Sociology, the American Sociological Review, and Social Forces were selected to best ensure that any trends identified actually reflect voluntarily decided interests among American sociologists from 1950 -the heyday of American sociology -to 2010.…”
Section: Samplementioning
confidence: 99%
“…Budd and colleagues (Budd & Seavey, 1996;Budd, 2000;Adkins & Budd, 2006) have conducted replication of institutional productive research for library and information science. For their three studies, Budd and colleagues used only Social Science Citation Index (SSCI) to rank programs.…”
Section: Related Literaturementioning
confidence: 99%
“…Budd and colleagues (Budd & Seavey, 1996;Budd, 2000;Adkins & Budd, 2006) have conducted a series of reviews of library information and science program rankings using Social Science Citation Index (SSCI). There has been an increase in research productivity at institutions in library information and science for individuals and programs.…”
Section: Related Literaturementioning
confidence: 99%
“…There has been an increase in research productivity at institutions in library information and science for individuals and programs. Adkins and Budd (2006) noted the potential bias that larger number of faculty could result in greater productivity. Although some specialties in the discipline are omitted from SSCI, they concluded that a productive program tends to remain productive, but some changes occur over time.…”
Section: Related Literaturementioning
confidence: 99%